2021
DOI: 10.1038/s41467-021-27060-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical C–N bond activation for deaminative reductive coupling of Katritzky salts

Abstract: Electrosynthesis has received great attention among researchers in both academia and industry as an ideal technique to promote single electron reduction without the use of expensive catalysts. In this work, we report the electrochemical reduction of Katritzky salts to alkyl radicals by sacrificing the easily accessible metal anode. This catalyst and electrolyte free platform has broad applicability to single electron transfer chemistry, including fluoroalkenylation, alkynylation and thiolation. The deaminative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…18, Method A). 64 Masson, Claraz and co-workers demonstrated coupling of Katritzky salts as well as NHP esters in yields up to 94%, including amino acid derived alkyl NHP esters (Fig. 18, Method B).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…18, Method A). 64 Masson, Claraz and co-workers demonstrated coupling of Katritzky salts as well as NHP esters in yields up to 94%, including amino acid derived alkyl NHP esters (Fig. 18, Method B).…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…The resulting radical carboxylate would thereafter undergo a second electron transfer to the corresponding enolate that decomposes to the gem-difluoroalkene product with release of fluoride (Figure Electroreductive C-F bond cleavage and concomitant functionalization of α-trifluoromethyl styrenes to gem-difluoroalkenes have recently been reported using radical precursors such as alkyl halides, redox active esters and Katritzky salts, as well as aryl halides (Figure 18). 64,65,66,67,68 Ni, Guo and Wang and co-workers demonstrated that Katritzky salts could be successfully used as coupling partners in DMSO under galvanostatic conditions with a sacrificial Zn anode and a Ni foam cathode, furnishing products in up to 85% yield (Figure 18, Method A). 64 Masson, Claraz and co-workers demonstrated coupling of Katritzky salts as well as NHP esters in yields up to 94%, including amino acid derived alkyl NHP esters (Figure 18, Method B).…”
Section: C-f Bond Cleavage In -Cf 3 Alkenesmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Their role as electron acceptors also formed the basis of the recent pioneering work of Watson, who in 2017 first reported deaminative radical couplings via single electron transfer (SET) to a 2,4,6triphenyl pyridinium (2), or "Katritzky salt", using low-valent nickel catalysis (Scheme 1A). 7 Since Watson's seminal reports, this area has seen tremendous growth and now also includes diverse examples employing nickel catalysis, 8 photoredox catalysis, 9 electrocatalysis, 10 and photoexcited electron donor-acceptor complexes, 11 with these strategies allowing formation of diverse carbon-carbon and carbon-heteroatom bonds from amine precursors. 12 However, a persistent limitation in this chemistry is the need for the 2,4,6-triphenylpyridinium salt.…”
mentioning
confidence: 99%